Mr. Robot. Season 4.0, the final season [videorecording (DVD)]. - Malek, Rami; Slater, Christian; Doubleday, Portia (Universal Pictures Home Entertainment, 2020)
Cyber-security engineer Elliot Anderson, along with the titular character and fsociety, starts a revolution to change the world. Season four will pick up where the third season finale left off, delving into the pros and cons of Elliot hitting 1send2 on the email that could reverse Five/Nine.